Platinum monatomic loaded nickel-vanadium layered double hydroxide electrocatalyst as well as preparation method and application thereof

The problem of low efficiency and poor stability of catalysts in alkaline electrolytic water is solved by synthesizing ultra-low Pt single-atomic loading of nickel-vana layered double hydroxide electrocatalysts in situ oxidation on nickel-vana layered double hydroxide support. , realizes efficient chlorine catalytic hydrogen adsorption under industrial current density.

CN119287405AActive Publication Date: 2025-01-10YUNNAN UNIV +2
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411409119.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-10
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

Under alkaline electrolytic conditions, during the process of electrolyzing seawater hydrogen production, the existing catalysts have low efficiency and poor stability, and the presence of chloride ions lead to a decrease in the performance of the electrocatalyst, making it difficult to maintain efficient catalytic activity under industrial current density.

Method used

Using nickel vanadium layered double hydroxide (NiV-LDH) as the carrier, the in-situ oxidation of chloroplatinic acid hexahydrate (H2PtCl6·6H2O) as the Pt source was used as a carrier. Vanadium layered double hydroxide (Pt1/NiV-LDH) electrocatalyst uses its ultra-thin nanosheet structure and high-valent transition metal doping to improve the stability and activity of the catalyst.

Benefits of technology

Under industrial current density, Pt1/NiV-LDH electrocatalyst exhibits excellent alkaline hydrogen adsorption (HER) catalytic activity and stability, can maintain efficient catalytic performance in a high chloride ion environment, significantly improving the production of hydrogen by electrolyzing water Efficiency and chlorine resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287405A_ABST
    Figure CN119287405A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalytic materials, and particularly relates to a platinum single atom loaded nickel-vanadium layered double hydroxide electrocatalyst as well as a preparation method and application thereof. The invention discloses a preparation method of a nickel-vanadium layered double hydroxide (Pt1 / NiV-LDH) electrocatalyst with ultralow platinum (Pt) monatomic loading capacity and an application of the electrocatalyst in chlorine-resistant hydrogen production under industrial current density. The Pt1 / NiV-LDH electrocatalyst is composed of a reaction active matter and a carrier, the reaction active matter is Pt monatomic, and the carrier is a nickel-vanadium layered double hydroxide nano material. The efficient Pt1 / NiV-LDH catalyst is designed and synthesized by adopting a simple solvothermal method and taking H2PtCl6. 6H2O as a Pt source through in-situ oxidation, and the catalyst shows excellent electro-catalytic hydrogen evolution (HER) performance in an alkaline electrolyte; and the catalyst has high quality activity, shows excellent alkaline HER catalytic activity and stability under industrial current density, and is suitable for market popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalytic materials, and relates to a nickel-vanadium layered double hydroxide electrocatalyst loaded with platinum single atoms, and a preparation method and application thereof, and specifically relates to a preparation method of a nickel-vanadium layered double hydroxide (Pt1 / NiV-LDH) electrocatalyst with ultra-low Pt single atom loading, and an application thereof in chlorine-resistant hydrogen production under industrial current density. Background Art

[0002] As a new type of green and zero-carbon clean energy, hydrogen energy plays an important role in achieving carbon peak and promoting carbon neutrality. As an important way to produce "green hydrogen", water electrolysis is limited by the shortage of fresh water resources, so researchers turned their attention to the abundant reserves of seawater, but the complex composition of seawater has brought many challenges to direct hydrogen production technology. Under electrolysis conditions, the insoluble precipitates and chloride ions produced lead to low efficiency and poor stability of the electrocatalyst. In addition, there are no hydrogen protons in alkaline electrolytes, and the protons required for adsorption must be provided by water molecules. The increased water dissociation step in this alkaline environment also severely limits the efficiency of HER. Therefore, it is of great significance to develop efficient HER catalysts for use under high current density and direct electrolysis of seawater.

[0003] Among many catalysts, single atom catalysts (SACs) not only have extremely low metal loading and atom utilization close to 100%, but also have ultra-high selectivity due to their unique electronic and geometric structures. In addition, the strong interaction between atoms and metal carriers can accelerate the transfer of charge during the catalytic reaction and improve the catalytic activity. These advantages make them a research hotspot. However, the surface free energy of single atoms is relatively high. In the actual reaction process, isolated atoms can easily migrate and agglomerate into clusters or nanoparticles, which affects the catalytic performance of the catalyst. Therefore, finding suitable carrier materials to reduce or avoid the migration and agglomeration of single atoms is the key to achieving the catalytic performance of SACs. Summary of the invention

[0004] In view of this, the present invention discloses a nickel-vanadium layered double hydroxide electrocatalyst loaded with platinum single atoms, a preparation method and an application thereof, and specifically discloses a preparation method of a nickel-vanadium layered double hydroxide (Pt1 / NiV-LDH) electrocatalyst with ultra-low Pt single atom loading and an application thereof in chlorine-resistant hydrogen production at industrial current density.

[0005] It should be noted that nickel-based layered double hydroxide (Ni-LDH) is conducive to stabilizing noble metal single atoms with high intrinsic activity due to its stable layered structure, adjustable components, rich active sites and large amount of surface oxygen on the surface. In addition, doping with high-valent transition metal vanadium (V) can stabilize the surface oxygen of Ni-LDH to prevent structural collapse, and can also attract surrounding electrons to effectively adjust the electronic structure of adjacent 3d metals, and change the d-band center of transition metal-based catalysts to optimize the adsorption and desorption of catalytic reaction intermediates by each metal active site of the catalyst, thereby improving the catalytic performance of the active site. Loading noble metal single atoms on V-doped Ni-LDH (NiV-LDH) carriers can greatly improve the stability of single-atom catalysts and maximize the unique advantages of each metal active center to enhance the catalytic activity of the catalyst. Based on the above reasons, it is feasible to design and prepare electrocatalysts that disperse Pt single atoms in ultrathin NiV-LDH nanosheets to enhance their catalytic activity and stability in hydrogen production by water electrolysis, which is also a technical problem that needs to be solved urgently.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] The first technical purpose of the present invention is to provide a method for preparing a nickel-vanadium layered double hydroxide electrocatalyst loaded with a single platinum atom, comprising the following steps:

[0008] Step (1): Pre-treat the NF and cut it into 2×4 cm 2 The NFs were immersed in hydrochloric acid, ultrasonicated in deionized water, and finally ultrasonicated in ethanol, and then naturally air-dried for later use;

[0009] Step (2): dissolving chloroplatinic acid in an ethylene glycol solution containing urea, and then mixing the solution with a deionized water solution containing nickel nitrate and vanadium trichloride and stirring uniformly;

[0010] Step (3): immersing the NF pretreated in step (1) into the mixed solution obtained in step (2), and then transferring to a polytetrafluoroethylene-lined stainless steel reactor for reaction;

[0011] Step (4): After the reaction in step (3) is completed, the obtained sample is rinsed with deionized water and ethanol for several times, and then vacuum dried to finally obtain a Pt1 / NiV-LDH electrocatalyst loaded on NF.

[0012] Optionally, the immersion ultrasonic operation in step (1) is as follows: firstly, a 2×4 cm 2 The NFs were immersed in 3 mol / L hydrochloric acid and sonicated for 15 min, then in deionized water for 6 min, and finally in ethanol for 5 min.

[0013] Optionally, in step (2), the mass ratio of chloroplatinic acid to urea is 0.01:0.12, the mass volume ratio of urea to ethylene glycol solution is 120 mg:20 mL, and the total amount of nickel nitrate and vanadium trichloride ions is 1.6 mmol.

[0014] Optionally, the reaction temperature in step (3) is 120° C. and the reaction time is 12 h.

[0015] Specifically, the steps include:

[0016] Step (1): Pre-treat the NF by first cutting it into a size of 2×4 cm 2 The NF was immersed in 3 mol / L hydrochloric acid for 15 min, then ultrasonicated in deionized water for 6 min, and finally ultrasonicated in ethanol for 5 min, and then naturally air-dried for use;

[0017] Step (2): 0.01 g of H2PtCl6·6H2O was dissolved in 20 mL of ethylene glycol solution containing 120 mg of urea, and then the solution was mixed with 20 mL of deionized water solution containing Ni(NO3)2·6H2O and VCl3 (total number of ions was 1.6 mmol) and stirred evenly;

[0018] Step (3): immersing the pretreated NF in the mixed solution obtained in step (2), then transferring it to a 100 mL polytetrafluoroethylene-lined stainless steel reactor, and reacting it at 120° C. for 12 h;

[0019] Step (4): After the reaction in step (3) is completed, the obtained sample is rinsed with deionized water and ethanol for several times, and then vacuum dried for 6 hours to finally obtain the Pt1 / NiV-LDH electrocatalyst loaded on the NF.

[0020] The present invention adopts a simple solvothermal method to design and synthesize a highly efficient Pt1 / NiV-LDH catalyst by in-situ oxidation with H2PtCl6·6H2O as a Pt source, and the catalyst exhibits excellent HER performance in a series of alkaline electrolytes such as 1M KOH, 1M KOH+0.5 / 1.0 / 2.0M NaCl, and 1M KOH+natural seawater; and the electrocatalyst synthesized by the present invention has an initial potential of almost zero in an alkaline medium and a time-delay of 20.98s at an overpotential of 200mV. -1 The ultra-high turnover frequency (TOF) value is 3.8 times that of commercial Pt / C, and its mass activity is 9 times that of commercial Pt / C electrodes. It also exhibits excellent alkaline HER catalytic activity and stability at industrial current density.

[0021] It should be noted that the nanomaterial electrocatalyst prepared by the present invention has a larger specific surface area and a higher density of catalytic active sites compared to traditional bulk electrocatalysts, and thus has a more excellent electrocatalytic activity. However, general nanomaterial electrocatalysts are prone to dissolution in strong acid or strong base electrolytes, resulting in loss of active components and reduced stability, while multi-level superstructure nano electrocatalysts with nano-microstructures composed of ultra-small or ultra-thin nanomaterials can overcome this shortcoming. The multi-level superstructure nano electrocatalyst not only has a high density of active sites, but also has structural stability similar to that of bulk materials, which will be beneficial to the improvement of electrocatalytic performance.

[0022] Furthermore, the volcano plot describes the relationship between the catalytic activity of a material and the hydrogen adsorption free energy of the material. Pt is very close to the top of the volcano plot curve and has a suitable hydrogen adsorption free energy, so Pt-based electrocatalysts generally exhibit ultra-high catalytic activity in the HER process. In addition, thanks to the unique electronic structure of Pt, its 5d orbital is located at the farthest position from the Fermi level, which is conducive to the transmission and migration of electrons through Pt, thereby improving the electron transfer between the surface active sites and the reactants, making it easier for the reaction intermediates to adsorb on its surface to form activated intermediates.

[0023] The second technical purpose of the present invention is to provide a nickel-vanadium layered double hydroxide electrocatalyst loaded with a single platinum atom prepared by the above method, wherein the electrocatalyst is a nickel-vanadium layered double hydroxide Pt1 / NiV-LDH, and the electrocatalyst is an ultra-thin nanosheet NiV-LDH loaded with a single Pt atom, that is, an ultra-thin NiV-LDH nanosheet modified with a single Pt atom; the Pt1 / NiV-LDH electrocatalyst is composed of a reaction active substance and a carrier, wherein the reaction active substance is a single Pt atom, and the carrier is a nickel-vanadium layered double hydroxide nanomaterial;

[0024] Moreover, the electrocatalyst uses a conductive substrate nickel foam (NF) as a self-supporting carrier and is synthesized by in-situ oxidation using a simple solvothermal method with hexahydrate chloroplatinic acid (H2PtCl6·6H2O) as a Pt source.

[0025] The present invention designs and synthesizes a highly efficient Pt1 / NiV-LDH catalyst by in-situ oxidation using H2PtCl6·6H2O as a Pt source using a simple solvothermal method. The catalyst exhibits excellent electrocatalytic hydrogen evolution (HER) performance in an alkaline electrolyte. The catalyst has high mass activity and exhibits excellent alkaline HER catalytic activity and stability at industrial current density, and is suitable for market promotion and application.

[0026] The third technical purpose of the present invention is to provide a nickel-vanadium layered double hydroxide electrocatalyst loaded with platinum single atoms prepared by the above method and used in electrocatalytic hydrogen production.

[0027] Specifically, the nickel-vanadium layered double hydroxide electrocatalyst loaded with platinum single atoms is used for chlorine-resistant hydrogen production at industrial current density.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The present invention discloses a method for preparing a nickel-vanadium layered double hydroxide (Pt1 / NiV-LDH) electrocatalyst with ultra-low Pt single atom loading and its application in chlorine-resistant hydrogen production under industrial current density; the material is an ultra-thin nanosheet NiV-LDH loaded with Pt single atoms (Pt1 / NiV-LDH), the electrocatalyst uses a conductive substrate nickel foam (NF) as a self-supporting carrier, and adopts a simple solvothermal method to perform in-situ oxidation synthesis using hexahydrate chloroplatinic acid (H2PtCl6·6H2O) as a Pt source.

[0030] (2) The present invention uses a Pt1 / NiV-LDH self-supporting electrode, which avoids the difficulty of charge transfer caused by the use of adhesives, which leads to the blocking of active sites and the increase of interface resistance, as well as the possibility of degradation of the adhesive itself to produce uncontrollable side reactions. In addition, the Pt1 / NiV-LDH electrocatalyst only needs 207mV overpotential in 1M KOH+2M NaCl solution to achieve 2000mAcm -2 In 1 M KOH seawater solution, the Pt1 / NiV-LDH electrocatalyst only needs 130 and 215 mV overpotentials to achieve 1000 and 2000 mA cm, respectively. -2 Industrial-grade current density, and at 500mA cm -2 The anion exchange membrane electrolyzer (AEMWE) assembled with Pt1 / NiV-LDH as the cathode electrode can achieve 500 and 1000 mA cm at low voltages of only 1.55 and 1.62 V, respectively. -2 The current density is 2.17 W, which shows that the nickel-vanadium layered double hydroxide (Pt1 / NiV-LDH) electrocatalyst with ultra-low Pt single atom loading prepared by the present invention has great practical application potential.

[0031] In summary, the Pt1 / NiV-LDH electrocatalyst exhibits excellent chlorine resistance during the electrolysis of seawater, and exhibits excellent alkaline HER catalytic activity and stability at industrial-grade current density. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0033] Figure 1 This is the preparation flow chart of Pt1 / NiV-LDH electrocatalyst.

[0034] Figure 2 X-ray diffraction and Raman spectra of NiV-LDH and Pt1 / NiV-LDH electrocatalysts.

[0035] Figure 3 In the figure, ab) are spherical aberration electron microscopy of Pt1 / NiV-LDH electrocatalyst; c) is the fitting of Pt single atom X-ray fine absorption spectrum; dh) is the element mapping spectrum of each component of Pt1 / NiV-LDH electrocatalyst.

[0036] Figure 4 Scanning electron microscope images of Pt1 / NiV-LDH electrocatalysts with different Pt contents.

[0037] Figure 5 a) Polarization curve for evaluating the performance of hydrogen production by electrolysis of water under high current density of Pt1 / NiV-LDH electrocatalysts with different Pt contents; b) Histogram for evaluating the performance of hydrogen production by electrolysis of water under Pt1 / NiV-LDH electrocatalysts with different Pt contents.

[0038] Figure 6 Comparison of polarization curves of Pt1 / NiV-LDH electrocatalyst and commercial Pt / C electrocatalyst before and after cycle stability test.

[0039] Figure 7 Catalytic performance (a) and stability (b) of anion exchange membrane electrolyzer (AEM) assembled with Pt1 / NiV-LDH catalyst and NiFe-LDH.

[0040] Figure 8 Polarization curves of the catalytic performance of Pt1 / NiV-LDH catalyst in the electrolysis of brine (a) and alkaline seawater (b). DETAILED DESCRIPTION

[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] The word "embodiment" used here as an "exemplary" does not necessarily mean that any embodiment described is superior to or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this application are performed using conventional test methods in the art. It should be understood that the terms described in this application are only used to describe specific implementation methods and are not used to limit the content disclosed in this application.

[0043] Unless otherwise specified, the technical and scientific terms used in this document have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs; other experimental methods and technical means not specifically specified in this application refer to experimental methods and technical means commonly used by ordinary technicians in this field.

[0044] In order to better illustrate the content of the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present application.

[0045] Under the premise of no conflict, the technical features disclosed in the embodiments of the present application can be combined arbitrarily, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present application.

[0046] The present invention discloses a nickel-vanadium layered double hydroxide electrocatalyst loaded with platinum single atoms, a preparation method and an application thereof, and specifically relates to a preparation method of a nickel-vanadium layered double hydroxide (Pt1 / NiV-LDH) electrocatalyst with ultra-low Pt single atom loading and an application thereof in chlorine-resistant hydrogen production at industrial current density.

[0047] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.

[0048] Example 1

[0049] A method for preparing an ultrathin NiV-LDH nanosheet (Pt1 / NiV-LDH) electrocatalyst modified with a single Pt atom, the specific process is as follows Figure 1 As shown, the following steps are included:

[0050] Step (1): Pre-treat the NF by first cutting it into a size of 2×4 cm 2 The nickel foam was immersed in 3M hydrochloric acid for 15 minutes, then ultrasonicated in deionized water for 6 minutes, and finally ultrasonicated in ethanol for 5 minutes, and then naturally air-dried for use;

[0051] Step (2): Dissolve 0.01 g H2PtCl6·6H2O in 20 mL ethylene glycol solution containing 120 mg urea. Then, mix the above solution with an aqueous solution containing Ni(NO3)2·6H2O and VCl3 (total ion content 1.6 mmol) and stir evenly;

[0052] Step (3): immersing the pretreated NF into the mixed solution obtained in step (2), and then transferring it to a 100 mL polytetrafluoroethylene-lined stainless steel reactor, and reacting it at 120° C. for 12 h;

[0053] Step (4): After the reaction, the sample obtained was rinsed several times with deionized water and ethanol, respectively, and then vacuum dried for 6 hours to finally prepare the Pt1 / NiV-LDH electrocatalyst loaded on NF.

[0054] Application Example 1: Testing the HER catalytic performance of Pt1 / NiV-LDH electrocatalyst in alkaline medium

[0055] like Figure 2-4 As shown, the crystal structure and microscopic morphology of the obtained Pt1 / NiV-LDH electrocatalyst were characterized, including X-ray diffraction, Raman, scanning electron microscopy, spherical aberration electron microscopy, and X-ray fine absorption spectroscopy. Through the above characterization, it was determined that Pt1 / NiV-LDH existed in the form of nanosheets, and the introduction of Pt did not change the crystal structure of NiV-LDH, and was fixed on the surface of NiV-LDH in the form of a single atom.

[0056] The HER performance of electrocatalysts such as Pt1 / NiV-LDH was tested in 1.0 M KOH solution. Figure 5 and Figure 6 As shown in Figure 2, Pt1 / NiV-LDH with a Pt content of 0.39 wt% (Pt1 / NiV-LDH) exhibits the best HER catalytic performance, requiring only 9 and 46 mV to achieve 10 and 100 mA cm, respectively. -2 In addition, the Pt1 / NiV-LDH catalyst can achieve 500 and 1000 mA cm-2 with an overpotential of only 84 and 130 mV, respectively. -2 The current density is much lower than that of NiV-LDH (322mV@500mA cm -2 、381mV@1000mA cm -2)、Pt / C electrode (181mV@500mA cm -2 、279mV@1000mA cm -2 ). Even at 2000mAcm -2 Even at an ultra-high current density, Pt1 / NiV-LDH only requires an extremely low overpotential of 243 mV, indicating its excellent HER catalytic activity. It also shows that the Pt1 / NiV-LDH catalyst has the potential for industrial application.

[0057] Application Example 2: Full Electrolysis Water Performance Test

[0058] In order to study the practical application potential of Pt1 / NiV-LDH catalyst in water electrolysis, Pt1 / NiV-LDH was used as cathode electrode, NiFe layered double hydroxide (NiFe-LDH) was used as anode electrode, and 1M KOH was used as electrolyte in AEMWE. Figure 7 As shown in Figure 2, at an operating temperature of 60°C, NiFe-LDH(+)||Pt1 / NiV-LDH(-) exhibits a low starting potential of 1.45V, and its current density can reach 500 and 1000mAcm at voltages of 1.55V and 1.62V, respectively. -2 , which is superior to most reported electrocatalysts.

[0059] In addition, when the operating temperature is 25℃, NiFe-LDH(+)||Pt1 / NiV-LDH(-) at 1000mAcm -2 It can work stably for about 100h at industrial current density ( Figure 7 ), although there is a slight attenuation, the attenuation rate is only 0.05mVh -1 , indicating that Pt1 / NiV-LDH has excellent stability and practical utility.

[0060] Application Example 3: Testing the HER catalytic performance of Pt1 / NiV-LDH electrocatalyst in alkaline seawater medium

[0061] The practical performance of Pt1 / NiV-LDH electrocatalyst for electrolysis of seawater was evaluated in alkaline seawater (1MKOH+0.5MNaCl) and alkaline natural seawater (1MKOH+seawater). Figure 8 As shown in Figure 2, the self-supported Pt1 / NiV-LDH electrocatalyst maintained excellent catalytic activity in 1M KOH + 0.5M NaCl solution, reaching 500 and 1000 mA cm at overpotentials of only 85 mV and 129 mV, respectively. -2 The current density of 2.5 W was 0.1 W, indicating its good tolerance to chloride ions.

[0062] In addition, the activity of Pt1 / NiV-LDH in 1M KOH solution with different Cl - The HER performance of the concentration was used to evaluate its corrosion resistance.

[0063] The test results show that: - Increase in concentration (≥1.0 MCl - ), the corresponding HER overpotential increases slightly, especially at low current densities (≤500mAcm -2 ). However, when the operating current density exceeds 1000mAcm -2 When Cl - The corrosion rate of Pt1 / NiV-LDH catalyst decreased significantly with the increase of its concentration, indicating that the Pt1 / NiV-LDH catalyst has good corrosion resistance.

[0064] In addition, the HER performance of the Pt1 / NiV-LDH catalyst in alkaline natural seawater (1MKOH+seawater) was evaluated.

[0065] The test results show that the Pt1 / NiV-LDH electrocatalyst has good performance at low and high current densities (from 10 to 2000 mA cm -2 ) still showed excellent catalytic activity, reaching 1000 and 2000 mA cm at overpotentials of only 130 and 215 mV, respectively. -2 The industrial current density is much lower than that of Pt / C (362mV@1000mAcm -2 , 551mV@2000mAcm -2 ), Pt foil (587mV@1000mAcm -2 , 851mV@2000mAcm -2 ), which all indicate that the Pt1 / NiV-LDH electrocatalyst exhibits efficient HER catalytic activity in the electrolysis of seawater. The present invention provides a new idea for the design and preparation of electrocatalysts for direct electrolysis of seawater.

[0066] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a nickel-vanadium layered double hydroxide electrocatalyst loaded with platinum single atoms, characterized in that: The method specifically comprises the following steps: Step (1): Pre-treat the NF and cut it into 2×4 cm 2 The NFs were immersed in hydrochloric acid, ultrasonicated in deionized water, and finally ultrasonicated in ethanol, and then naturally air-dried for later use; Step (2): dissolving chloroplatinic acid in an ethylene glycol solution containing urea, and then mixing the solution with a deionized water solution containing nickel nitrate and vanadium trichloride and stirring uniformly; Step (3): immersing the NF pretreated in step (1) into the mixed solution obtained in step (2), and then transferring to a polytetrafluoroethylene-lined stainless steel reactor for reaction; Step (4): After the reaction in step (3) is completed, the obtained sample is rinsed with deionized water and ethanol for several times, and then vacuum dried to finally obtain a Pt1 / NiV-LDH electrocatalyst loaded on NF.

2. The method for preparing the nickel-vanadium layered double hydroxide electrocatalyst loaded with platinum single atoms according to claim 1, characterized in that: The immersion ultrasonic operation in step (1) is as follows: first, a 2×4 cm 2 The NFs were immersed in 3 mol / L hydrochloric acid and sonicated for 15 min, then in deionized water for 6 min, and finally in ethanol for 5 min.

3. The method for preparing the nickel-vanadium layered double hydroxide electrocatalyst loaded with platinum single atoms according to claim 1, characterized in that: In step (2), the mass ratio of chloroplatinic acid to urea is 0.01:0.12, the mass volume ratio of urea to ethylene glycol solution is 120 mg:20 mL, and the total amount of nickel nitrate and vanadium trichloride ions is 1.6 mmol.

4. The method for preparing the nickel-vanadium layered double hydroxide electrocatalyst loaded with platinum single atoms according to claim 1, characterized in that: The reaction temperature in step (3) is 120° C. and the reaction time is 12 h.

5. A nickel-vanadium layered double hydroxide electrocatalyst loaded with single platinum atoms prepared by the method of claim 1, characterized in that: The electrocatalyst is nickel-vanadium layered double hydroxide Pt1 / NiV-LDH, and the electrocatalyst is an ultrathin nanosheet NiV-LDH loaded with Pt single atoms, that is, an ultrathin NiV-LDH nanosheet modified with Pt single atoms; and the electrocatalyst uses a conductive substrate nickel foam (NF) as a self-supporting carrier, and adopts a simple solvothermal method to perform in-situ oxidation synthesis using hexahydrate chloroplatinic acid (H2PtCl6·6H2O) as a Pt source.

6. Use of the nickel-vanadium layered double hydroxide electrocatalyst loaded with single platinum atoms prepared by the method of claim 1 or the nickel-vanadium layered double hydroxide electrocatalyst loaded with single platinum atoms as claimed in claim 5 in electrocatalytic hydrogen production.

7. The use according to claim 6, characterized in that: The nickel-vanadium layered double hydroxide electrocatalyst loaded with platinum single atoms is used for chlorine-resistant hydrogen production at industrial current density.

Citation Information

Patent Citations

  • Preparation method of platinum / layered bimetal oxide methanol fuel cell catalyst

    CN105098201A

  • NiV-LDH-NF hydrogen production electrode with optimized electronic structure, and preparation method and application of NiV-LDH-NF hydrogen production electrode

    CN110760879A

  • Platinum monatomic catalyst and preparation method and application thereof

    CN113881961A

  • Method for preparing ultrathin cobalt vanadate nanosheet loaded metal monatomic catalyst

    CN114164452A

  • Low-platinum-load nickel-iron layered hydroxide electrolyzed water catalyst as well as preparation method and application thereof

    CN116949502A